Population of beneficial insect in immature and mature oil palm plantation in Felcra Seri Mendapat / Mohamad Amirul Norizan - Norizan, Mohamad Amirul (Faculty of Plantation and Agrotechnology, 2019)
This study was conducted to determine the population of beneficial insect in different oil palm age which is immature and mature oil palm. The objective is to determine and compare the population of beneficial insect in immature and mature oil palm plantation. Sampling was carried out from August to September 2018 at Felcra Sri Mendapat oil palm by using yellow sticky trap. A total of 468 individuals of beneficial insect from order Hymenopteran consisting of 11 families were successfully collected. The most abundant families recorded were family Ichneumonidae that make up of 96 individuals in both field. The least families recorded were Eucharitidae with only a total of 25 individuals in both fields. The T-test showed that they were no significance difference between the immature and mature oil palm field. This study is expected to be able to calculate the population of beneficial insect in both oil palm fields to help the management identify whether the beneficial insect population is able to counteract the population of insect pest.